Patterns of Volcanism in the Cascade Arc During the Past 15,000 Years - Scott, William (Geoscience Canada, 1990)
Summary About 110 well-dated and 70 poorly date deruptive periods less than 15,000 years old at individual volcanoes in the Cascade arc constitute a data set for identifying spatial and temporal patterns of eruptive activity. Key features of the record include: (1) the mean frequency of eruptive periods during the past 4,000 years is approximately two per century, however, the variance about the mean may belarge; (2) at most major centres, episodes of activity lasting several thousand years are defined by groups of eruptive periods separated by apparent dormant intervals of roughly similar duration, (3) arc-wide clustering of eruptive activity may exist at 0-4 ka, 6-8 ka, and 10-14 ka. Such clustering would be remarkable in light of significant along-arc changes in crustal structure, stress field, and subduct Ion-zone geometry.